BOOKS REVIEWE; THE VENTURE OF ISLAM: CONSCIENCE AND HISTORY IN A WORLD CIVILIZATION KARYA:MARSHALL G.S. HODGSON - Alfauzan Amin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The main ideas as an excellence book entitled The Venture of Islam Conscience and History in a World Civili- zation were prepared by Marshall GS Hodgson with a critical historical study. The book which consists of three volumes is interesting to review. Although other than the author is not a follower of Islam, the objective in analyzing the data in his study needs to be reviewed. The writing in the form of this review aims; 1) reviewing the aspects in which the work has strength both in terms of methodology, objectivity of data studies on Islamic history and 2) examining the weak- nesses of the analyst